The Application Of Digital Marketing Grabfood In Increasing Customer Loyalty In The City Of Bengkulu - Bintang, Muhammad Ilham; Indriasari, Nia; Zoniarti, Zoniarti (Jurnal Akuntansi, Manajemen dan Bisnis Digital, 2025)
In the era of digital transformation, the utilization of digital platforms is one of the main keys in reaching consumers and maintaining their loyalty. This research aims to analyze the application of digital marketing by GrabFood in increasing customer loyalty in Bengkulu city. This research uses qualitative methods with data collection techniques through interviews, observation and documentation. Determination of informants in this study using purposive sampling technique. The results showed that GrabFood Bengkulu has implemented digital marketing in the form of paid advertisements that appear on social media, promotions through social media instagram @grabsumbagsel, utilization of influencers in collaboration to create content marketing and loyalty programs in the form of GrabRewards points and discounts. From these forms of digital marketing, some are effective in reaching customers such as advertisements on social media and collaboration with influencers. In terms of attracting shopping interest, loyalty programs and digital rewards take a major role. Digital marketing by GrabFood Bengkulu has positive implications in increasing customer loyalty. A pleasant experience in the GrabFood purchase process, structured handling of order problems and refund processes, and customer rewards are factors in shaping GrabFood Bengkulu customer loyalty.